Morphological change and differential proteomics analysis of gill in Mytilus coruscus under starvation - Liang, Ze-Wei; Li, Si-Yuan; Zhang, Xiao-Lin; Chen, Chuan-Yue; Sun, Wen-Jing; Gu, Zhong-Qi; Huang, Ji; He, Jian-Yu; Qi, Peng-Zhi; Guo, Bao-Ying; Liao, Zhi; Yan, Xiao-Jun (Frontiers in Physiology, 2023)
Mytilus coruscus is a dominant shellfish in the Yangtze estuary and its adjacent sea area. Food deprivation often occurs during their growth due to fluctuations in algal abundance caused by seasonal freshwater flushing and high-density aquaculture mode. To investigate the coping strategies of M. coruscus to starvation stress, electron microscopy and differential proteomic analysis were performed on the critical feeding organ gill of the mussels after 9 days of starvation. The electron microscopy results showed that the cilia of the mussel gills were dissolved, and the gaps between gill filaments widened under starvation. Differential proteomic analysis revealed that phagocytosis-related proteins such as ATPeV1E, ATPeV1C, LAMP1_2 and CTSL were significantly upregulated, and the phagocytosis pathway was significantly enriched (P<0.05). In addition, the corin content in gill and myeloperoxidase level as well as the number of dead cells in blood were both significantly increased (P<0.05). What’s more, proteomic data suggested that immune maintenance, cellular transport and metabolism related pathways were significantly enriched, which illustrated an immune and metabolism responses under starvation. This study reveals for the first time that phagocytosis functions as an essential strategy for M. coruscus to cope with starvation, which provides new scientific knowledge and a theoretical basis for understanding the adaptation mechanisms of mussel to starvation and for rational optimization of mussel culture patterns.